Green pawn financing for MSMEs as an ESG-oriented transformation of pawnshop - Apriansyah, Muhammad Rifky; Amimah, Ahadina Hanifati; Prabowo, Aubry Fairuza Akifa (Journal of Entrepreneurial Economics, 2026)
Background: The transformation of the national financial sector following the implementation of Law No. 4/2023 and its derivative regulations, marks a new phase in strengthening the institutional role of Pegadaian as a key actor in microfinance in Indonesia. In the context of sustainability and ESG (Environmental, Social, and Governance), there is no pawn-based microfinance scheme that proactively targets green MSMEs, even though the potential and demand for green financial products continue to increase. Methods: This article aims to analyze the institutional feasibility and concept of Green Pawn Financing, which is a pawn financing scheme based on ESG principles, while identifying the potential and challenges of its implementation. This study uses a descriptive-analytical approach with a normative institutional review. Institutional innovation theory, sustainable regulatory frameworks, and green financial inclusion literature are used as the basis for analysis. Findings: The results of the study show that Pegadaian already has an adequate initial foundation through gold savings, electric vehicle loans, and a corporate ESG roadmap. However, the integration of ESG into pawn services is not yet systemic and does not explicitly target green MSMEs. This creates a strategic gap that "Green Pawn Financing" can fill by bridging national climate targets with micro-level operational realities within a conducive regulatory framework. Conclusion: The Green Pawn Financing concept offered includes interest and loan tenor incentives, light environmental audits based on emissions calculations, and the potential development of carbon pawn and sustainability certificate-based collateral. Regulatory-wise, this scheme is compatible with the national sustainability framework and has the potential to support green financing targets. Novelty/Originality of this article: This article contributes to positioning Green Pawn Financing as an instrument for domestic commodity-based (gold) micro green finance transition, which not only expands financial inclusion but also increases public trust in Pegadaian as a sustainable financial institution.